N-type voltage gated calcium channels mediate excitatory synaptic transmission in the anterior cingulate cortex of adult mice - Kang, SukJae Joshua (BioMed Central, 2013)
Voltage gated calcium channels (VGCCs) are well known for its importance in synaptic transmission in the peripheral and central nervous system. However, the role of different VGCCs in the anterior cingulate cortex (ACC) has not been studied. Here, we use a multi-electrode array recording system (MED64) to study the contribution of different types of calcium channels in glutamatergic excitatory synaptic transmission in the ACC. We found that only the N-type calcium channel blocker ω-conotoxin-GVIA (ω-Ctx-GVIA) produced a great inhibition of basal synaptic transmission, especially in the superficial layer. Other calcium channel blockers that act on L-, P/Q-, R-, and T-type had no effect. We also tested the effects of several neuromodulators with or without ω-Ctx-GVIA. We found that N-type VGCC contributed partially to (1S,3R)-1-aminocyclopentane-1,3-dicarboxylic acid- and (R)-Baclofen-induced synaptic inhibition. By contrast, the inhibitory effects of 2-Chloroadenosine and carbamoylcholine chloride did not differ with or without ω-Ctx-GVIA, indicating that they may act through other mechanisms. Our results provide strong evidence that N-type VGCCs mediate fast synaptic transmission in the ACC.